Comparison of thermal and electric characteristic for free-burning arc using coupled and decoupled sheath models. (22nd September 2017) - Sun, Qiang; Wang, Cheng; Chen, Tang; Xia, Wei-Dong
Abstract: A comparison of coupled and decoupled sheath models is performed to study the interaction between the arc column and the near cathode layer in this paper. The coupled model used in this paper is modified based on the previous work. The thermal conductions of the heavy particles and electrons between the arc column and the near cathode layer are added to the energy transport equation in the model, which is different from the decoupled model of cathode sheath and arc column. The simulation shows that: (1) The energy (due to thermal conductions) delivered from the arc column to the near cathode layer is always positive, and it increases as arc currents increase. (2) Compared with the decoupled model for free-burning arc (20–200 A currents) at the diffuse mode of the cathodic attachment, the total arc voltage of the coupled model is closer to the value of experiment. (3) The voltage drop of the near cathode layer calculated by the coupled mode is always lower than that calculated by the decoupled model. The differences increase as the arc current increases. The voltage drop of arc column calculated by the coupled mode is lower than that calculated by the decoupled model at low current, and the situation is opposite at high current. (4) The current distribution of coupled model along the cathode surface is more uniform. In additional, we compare our coupled model with another coupled sheath model. The results from the two coupled sheath models are in good agreement in high currents.